The Impact of COVID-19 Pandemic on Café Design Concept - Salsadilla Mutiara Lestari; Gusriyani Nur Azizah; Dessy Puspita Sari; Hanhan Maulana (Universitas Komputer Indonesia, 2021)
Indonesia is one of the countries that have confirmed cases of COVID-19 since March 11, 2020. Where all sectors are mainly engaged in the culinary and hospitality industry due to the implementation of Pembatasan Sosial Berskala Besar (PSBB) that there are health protocol rules implemented by the government and a new adjustment to the building concept design. Café shall make innovation to survive from this pandemic. The research method used direct physical observation and literature studies. So that it can be seen the design concept that is feasible in this New Normal. The results of this study indicate that the café design concept has changed in accordance with the application of health protocols in the New Normal so as to create a building that is able to adapt to new habits that keep social activities safe during the pandemic. The main concept applied is the application of open space concept in a building and technology that can support cafe facilities. In the use of this open space concept, apart from creating larger open spaces, more openings, for the sake of circulation and lighting, touchless sensor technology, and layout of furniture designs to produce a design concept in a café. Accordance with the conditions of the COVID-19 pandemic. Open space concept in the new normal period is to improve the quality of a building that is healthy and good in terms of aesthetics and functionality, but can still support the COVID-19 virus chain breaker program.